Genetic afterlives : Black Jewish indigeneity in South Africa - Tamarkin, Noah, 1977- (Theory in forms., 2020)
"GENETIC AFTERLIVES is an ethnography of how Lemba people in South Africa manage competing claims of Jewish ethnic and religious identity, African indigeneity, and South African citizenship. To ask who and what the Lemba people are is to cut to the central questions anthropologist and science and technology scholar Noah Tamarkin explores in this book: are the Lemba people Jews or Africans? Are these categories mutually exclusive? In the mid-1990s, genetic researchers concluded that the Lemba people are genetic Jews. The following year, this study was welcomed by the Lemba Cultural Association at the same conference the Association announced plans for a community center in Sweetwaters, South Africa, which the Lemba people claim as their ancestral home. Taken together, these two actions might appear contradictory: how could the Lemba people claim a diasporic Jewish identity, while at the same time claim African indigeneity? Against this assumption, Tamarkin launches two crucial arguments about the uses of genetic ancestry. In contemporary usage, DNA testing often reproduces national boundaries, promising researchers and consumers a group or individuals "single" origin, or the ability to divide one's genetic background into constitutive parts. In opposition to these uses of genetic ancestry, Tamarkin argues for a theory of Lemba "becoming," in which "origins were multiple, [and] movements were multidirectional." In this understanding, the pigeonholing of the Lemba as essentially African or essentially Jewish becomes irrelevant, as such understanding of ancestry privilege one set of ancestors, or one historical point, over another, rather than honoring origins and ancestry as a multivalent process. The second argument concerns what Tamarkin calls the "afterlives" of genetic testing. Questions about Lemba genetics are often framed from the perspective of genetic researchers, which Tamarkin dubs "claims of DNA." In this book, Tamarkin centers "claims made with DNA" as genetic information leaves the hands of geneticists and is put to use by the subjects of genetic research in social, political, and legal contexts. In doing so, Tamarkin centers Lemba people as producers of genetic knowledge, highlighting how genetic research proving Lemba-Jewish connections were utilized by Lemba people in their efforts to gain postaparthaid state recognition through claims to traditional leadership and land and difference"--